Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1111/j.1537-2995.1969.tb05528.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenine on Stored Erythrocytes Evaluated by Autologous and Homologous Transfusions

Abstract: Blood obtained from normal volunteers and stored in ACD with or without adenine was evaluated by both tests in vitro and by 24-hour recovery following transfusion. Significant differences between autologous and homologous transfusions were not detected. The changes that did occur were limited to evidence of lesser erythrocyte breakdown in ACD units fortified with adenine. These units were associated with higher survival values at all storage periods evaluated and displayed over 70 per cent 24-hour posttrans'us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It is well known that CPDA-1 extends the survival days of stored RBCs by providing adenine for maintaining cytoplasmic ATP levels 1 38 . Our results clearly show that distinct trends in stored RBCs - the morphological transformation from discocytes to spherocytes as well as a decrease in membrane deformability – were considerably reduced in the presence of CPDA-1 at the individual cell level.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It is well known that CPDA-1 extends the survival days of stored RBCs by providing adenine for maintaining cytoplasmic ATP levels 1 38 . Our results clearly show that distinct trends in stored RBCs - the morphological transformation from discocytes to spherocytes as well as a decrease in membrane deformability – were considerably reduced in the presence of CPDA-1 at the individual cell level.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has been assumed that the decrease in transfusion recovery related to storage is due to RBC damages that accumulate after several weeks of storage. Studies performed more than 50 years ago have shown indeed that the extent of the storage lesion increases with storage duration while transfusion recovery decreases accordingly ( 5 , 8 , 10 , 45 ). Few studies have directly explored the correlation between in vitro markers of storage lesion and in vivo recovery.…”
Section: Storage Lesion Transfusion Recovery and Spleen Filtrationmentioning
confidence: 99%
“…Whole blood was stored in CPDA-1 bags. This anticoagulant present in the collection bag is composed of Citrate (chelates ionized calcium that prevents coagulation), Dextrose (a source of energy for the red blood cells), phosphate containing anticoagulants (lower acidity than other anticoagulants without phosphate and have a higher concentration of 2,3 DPG and red cell phosphate) and Adenine (ATP content and posttransfusion viability of red cells regenerated by addition of adenine) [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Citrate phosphate dextrose adenine solution was developed in 1968 and shown to permit whole-blood storage for 5 weeks [5]. Most blood collection bags (adult) contain 63 ml CPDA anticoagulant which is sufficient to anticoagulate and ensure the viability of blood cells in 450 ml ±10% blood for up to 28-35 days when the blood is stored at 2-8°C [6].…”
Section: Methodsmentioning
confidence: 99%